Gasto energético de repouso e transplante hepático: análise metabólica e nutricional antes e no decorrer de um ano após a operação - Livia Garcia Ferreira (2013)
Patients on the waiting list and undergoing liver transplantation (LTx) may present with changes in the resting energy expenditure (REE) as the liver is the primary organ of human metabolism. The aim of this study was to assess the REE before and during one year after LTx. The prevalence of changes in resting metabolism, associated factors and energy balance (EB) were also assessed. The REE was measured by indirect calorimetry and predicted by the Harris and Benedict formula (REEHB), before and 30, 90, 180, 270 and 370 days after LTx. Nutritional status was assessed by different methods. EB was obtained by subtracting the energy intake (obtained by 3 -day food record) from the total energy expenditure. Socioeconomic and clinical data were also evaluated. Simple and multiple regression analyses were performed (p<0.05). A total of 81 patients before and 17 assessed throughout one year after LTx, were enrolled in this study. Before LTx, 24.7% of the patients were considered hypermetabolic (REE:REEHB>1.2), and 7.4% hypometabolic (REE:REEHB<0.8). Malnourished patients had low REE and hyper - and hypometabolism were not associated with the nutritional status. The hypermetabolism was associated with higher values of glucose, and hypometabolism with higher values of INR. The EB was negative in 81.6% of patients and was associated with the severity of liver disease (Child-Pugh criteria). Before LTx, REE was associated with intracellular body water, arm muscle area and glucose serum. After LTx, REE was associated with triceps skinfold thickness, cumulative dose of prednisone and own REE before transplantation. There were increases in body weight, fat mass, handgrip strength, phase angle, fat intake and positive EB after LTx. The prevalence of hyper- and hypometabolism at one year of LTx was 11.8% of each. The presence of hypermetabolism after LTx was associated with the presence of hypermetabolism before transplantation and the cumulative dose of prednisone. Fat mass before transplantation and percentage of fat intake were associated with hypometabolism. Therefore, to assess the REE and the changes in resting metabolism of patients before and after transplantation is of utmost importance to maximize the benefits of nutritional therapy. Adequate and individualized nutritional guidance should start as early as possible.